2021
DOI: 10.2147/dddt.s306371
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological Management of Gastro-Esophageal Reflux Disease: An Update of the State-of-the-Art

Abstract: Gastro-esophageal reflux disease (GERD) is a highly prevalent, chronic disorder, whose knowledge remains limited and the management of these patients changes continuously. This review provides a summary of the most recent advancements in the pathogenesis of this disease and the new drugs introduced into the market to overcome some of the unmet needs of traditional therapies. Nowadays, the most fruitful diagnostic examinations are 24hour impedance-pH monitoring, which allows us to separate true NERD from esopha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
30
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(39 citation statements)
references
References 100 publications
0
30
0
Order By: Relevance
“…Patients who failed to obtain satisfactory symptomatic response or complete esophageal healing after a full course of standard dose PPI are defined as having PPI failure; a definition that allows inclusion of patients who perceived their remaining symptoms on PPI therapy as bothersome. 4 , 5 , 6 A study in 11,064 patients with chronic heartburn found that, although PPIs were the preferred class of medications for preventing heartburn, only 58% of PPI recipients reported being totally satisfied with their anti‐reflux treatment. 7 A systematic review that included 9 studies of 14,774 patients showed improved health‐related quality of life in patients who responded well to PPI treatment, but not in nonresponders.…”
mentioning
confidence: 99%
“…Patients who failed to obtain satisfactory symptomatic response or complete esophageal healing after a full course of standard dose PPI are defined as having PPI failure; a definition that allows inclusion of patients who perceived their remaining symptoms on PPI therapy as bothersome. 4 , 5 , 6 A study in 11,064 patients with chronic heartburn found that, although PPIs were the preferred class of medications for preventing heartburn, only 58% of PPI recipients reported being totally satisfied with their anti‐reflux treatment. 7 A systematic review that included 9 studies of 14,774 patients showed improved health‐related quality of life in patients who responded well to PPI treatment, but not in nonresponders.…”
mentioning
confidence: 99%
“…Due to the ability of binding bile salts, it could be of help also in WAR and/or WalkR. A new class of disposable medical agents, made up of a bioadhesive formulation of hyaluronic acid and chondroitin sulfate, was recently shown to improve symptoms and quality of life as an add-on therapy to PPI when compared to PPI alone in patients with NERD ( 125 , 126 ). Despite their use in patients with rGERD not having been evaluated yet, they could be of help in some patients because they target an additional pathophysiological mechanism.…”
Section: Therapy Of Rgerdmentioning
confidence: 99%
“…Potassium, phosphorus, magnesium, and other minerals present in horned melon pulp are significant for nerve transmission, muscle contraction, blood clotting, blood pressure regulation, immune system health, etc. [14].…”
Section: Horned Melon Pulpmentioning
confidence: 99%